Trypanosomatid parasites infecting managed honeybees and wild solitary bees. Issue 8 (July 2019) - Strobl, Verena; Yañez, Orlando; Straub, Lars; Albrecht, Matthias; Neumann, Peter
Graphical abstract: Highlights: Solitary bees Osmia cornuta can host trypanosomatid parasites, Crithidia mellificae, known from honeybees, Apis mellifera. C. mellificae reduced survival of A. mellifera workers, suggesting a mechanism for honeybee colony mortality. Our study supports a faecal – oral route of C. mellificae transmission. Male O. cornuta appear to be more susceptible to C. mellificae infections than females. Abstract: The parasite Crithidia mellificae (Kinetoplastea: Trypanosomatidae) infects honeybees, Apis mellifera . No pathogenic effects have been found in individual hosts, despite positive correlations between infections and colony mortalities. The solitary bee Osmia cornuta might constitute a host, but controlled infections are lacking to date. Here, we challenged male and female O. cornuta and honeybee workers in laboratory cages with C. mellificae . No parasite cells were found in any control. Parasite numbers increased 6.6 fold in honeybees between days 6 and 19 p.i. and significantly reduced survival. In O. cornuta, C. mellificae numbers increased 2–3.6 fold within cages and significantly reduced survival of males, but not females. The proportion of infected hosts increased in O. cornuta cages with faeces, but not in honeybee cages without faeces, suggesting faecal – oral transmission. The data show that O. cornuta is a host of C. mellificae and suggest that males are more susceptible. The higher mortality of infected honeybees proposes a mechanism for correlations between C. mellificae infections and colony mortalities.